Uji Efektifitas Bakteri Antagonis Untuk Pengendalian Penyakit Layu pada Tanaman Stroberi - ASADDIARI, SHAH KANIGARA; WIRYA, GUSTI NNGURAH ALIT SUSANTA; SIADI, I KETUT; SUDANA, I MADE (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2020)
Effectiveness Test of Antagonistic Bacteria to Control Strawberry Wilt Disease Strawberry (Fragaria sp.) Is a herbaceous fruit plant that was first discovered  in Chile, USA. Bali Province is one of the provinces that produce strawberries in Indonesia. The development center for strawberry commodity in the Province of Bali is in the Bedugul area, that is in the Village of Pancasari, District of Sukasada and Village of Candikuning, District of Tabanan. Since 2016, there have been quite harmful disorders in strawberry plants in Bali due to wilting caused by the fungus Fusarium oxysporum. Research on the effectiveness test of antagonistic bacteria to control strawberry wilt disease was conducted in January 2019 to August 2019. The purpose of this study was to determine the ability of antagonistic bacteria to control the growth of wilt disease in strawberries in vivo. The method used is the isolation of bacteria and pathogens, application of bacterial and pathogenic isolates, and observation. The results of this study are that the P3 bacterial isolate is able to control the most effective pathogens with a disease percentage of 20 %.